2008
DOI: 10.1073/pnas.0711324105
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of inositol 1,4,5-trisphosphate receptors by protein kinase B/Akt inhibits Ca 2+ release and apoptosis

Abstract: Imbalance of signals that control cell survival and death results in pathologies, including cancer and neurodegeneration. Two pathways that are integral to setting the balance between cell survival and cell death are controlled by lipid-activated protein kinase B (PKB)/Akt and Ca 2؉ . PKB elicits its effects through the phosphorylation and inactivation of proapoptotic factors. Ca 2؉ stimulates many prodeath pathways, among which is mitochondrial permeability transition. We identified Ca 2؉ release through inos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
172
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 236 publications
(185 citation statements)
references
References 37 publications
11
172
1
1
Order By: Relevance
“…In this respect, the slightly but consistently higher expression of CD22, an inhibitory coreceptor involved in Ca 2+ -flux [40], on unstimulated Akt1 Tg B cells could also contribute to their reduced Ca 2+ -release. It is also possible that enhanced Akt1 signals more directly influence Ca 2+ -release since cross-regulation between PI3K/Akt and Ca 2+ -signaling and modulation of the release and effects of calcium by Akt, thereby attenuating signaling, has been shown for other cell types [41].In contrast to NFATc1 and NF-κB/p65, expression and activation of STAT5 was strongly enhanced in α-IgM-stimulated Akt1 Tg B cells. In response to IL-7 signals, STAT5 regulates the survival and proliferation of B-cell progenitors and plays an important role in the generation of B-cell leukemia and lymphoma [36,42].…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…In this respect, the slightly but consistently higher expression of CD22, an inhibitory coreceptor involved in Ca 2+ -flux [40], on unstimulated Akt1 Tg B cells could also contribute to their reduced Ca 2+ -release. It is also possible that enhanced Akt1 signals more directly influence Ca 2+ -release since cross-regulation between PI3K/Akt and Ca 2+ -signaling and modulation of the release and effects of calcium by Akt, thereby attenuating signaling, has been shown for other cell types [41].In contrast to NFATc1 and NF-κB/p65, expression and activation of STAT5 was strongly enhanced in α-IgM-stimulated Akt1 Tg B cells. In response to IL-7 signals, STAT5 regulates the survival and proliferation of B-cell progenitors and plays an important role in the generation of B-cell leukemia and lymphoma [36,42].…”
mentioning
confidence: 64%
“…In this respect, the slightly but consistently higher expression of CD22, an inhibitory coreceptor involved in Ca 2+ -flux [40], on unstimulated Akt1 Tg B cells could also contribute to their reduced Ca 2+ -release. It is also possible that enhanced Akt1 signals more directly influence Ca 2+ -release since cross-regulation between PI3K/Akt and Ca 2+ -signaling and modulation of the release and effects of calcium by Akt, thereby attenuating signaling, has been shown for other cell types [41].…”
Section: Discussionmentioning
confidence: 99%
“…By using specific subcellular-targeted PTEN chimeras, we demonstrated that the effects of PTEN on Ca 2 þ homeostasis could not be ascribed to its regulation of PIP3 levels and subsequent Akt activation at the plasma membrane. 23,24,36,37 Indeed, the plasma membrane-targeted snap25-PTEN chimera displayed the higher reduction in Akt phosphorylation but no difference in [Ca 2 þ ] m . We demonstrated that ER-targeted PTEN markedly increases the [Ca 2 þ ] m transients, and we found that this correlate with a more effective reduction of pAkt Ser473 levels at the ER, in comparison with overexpression of wild-type PTEN.…”
Section: Discussionmentioning
confidence: 96%
“…Akt can phosphorylate all IP3R isoforms, 36,37 and a specific activity of Akt on IP3R3 leads to diminished ER-to-mitochondria Ca 2 þ transfer and protection from apoptosis. 19,24 The functional importance of PTEN interaction with IP3R3 is highlighted by the demonstration that, during apoptotic stimulation, the enhanced ER localization of PTEN positively correlated with an increased interaction with IP3R3, whereas Akt amount and phosphorylation levels as well as IP3R3 phosphorylation were reduced.…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of specific accessory proteins has been demonstrated to either positively or negatively regulate IP 3 R opening, with consequent alteration of cellular Ca 2+ signals (e.g. [25,26]). Although most of the data exploring IP 3 R-binding proteins has been derived from studies of neuronal IP 3 Rs, it is likely that cardiac IP 3 Rs form similar macromolecular complexes.…”
Section: The Abc Of Ip 3 : Where Does It Come From and Where Does It Go?mentioning
confidence: 99%